Perception Of Sexual Harassment Among Employees At The Managerial And Supervisory Level - Syed Harun, Sharifah Salmah (2001)
The research has explored the perception of sexual harassment among the employees at managerial and supervisory level and provided an understanding of the phenomena. Selected factors have been examined to further explore on the relationship and influence to the dependent variable, which is perception of sexual harassment.This study has confirmed that there is a positive relationship between exposures to sexual harassment information to perception of sexual harassment.